Colonoscopy findings of lower gastrointestinal bleeding in a tertiary care hospital: a 5-year retrospective study - Karki, Sanjit; Shrestha, Roshan; Sharma, Yuba Raj; Gautam, Sanjeev (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Malignancy is one of the aetiologies of lower gastrointestinal bleeding (LGIB). Colonoscopy is the diagnostic modalities of choice. In this study we aim to examine the common causes and prevalence of malignancy among patients presenting with LGIB. Method: This is descriptive retrospective study. We reviewed data of patients undergoing colonoscopy in Patan Hospital during January 2015 to December 2019. Result: Total 502 patients were included in the study. Hemorrhoids (49.4%,246) were common findings followed by normal findings (21.8%, 109), colonic polyps (7.8 %, 39) and Colorectal malignancy (4.2%, 21). 85 % (18/21) were left sided malignancies. 7.11% (5/21) of had age less than 40 years. Conclusion: Hemorrhoids were the most common cause and account nearly half of LGIB cases. Left sided colorectal malignancy can present with LGI bleeding, and not uncommon even in patients less than 40 years.